2015
DOI: 10.1534/genetics.115.176669
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Ejaculate by Drosophila melanogaster Females Requires the Male-Derived Mating Plug Protein PEBme

Abstract: Within the mated reproductive tracts of females of many taxa, seminal fluid proteins (SFPs) coagulate into a structure known as the mating plug (MP). MPs have diverse roles, including preventing female remating, altering female receptivity postmating, and being necessary for mated females to successfully store sperm. The Drosophila melanogaster MP, which is maintained in the mated female for several hours postmating, is comprised of a posterior MP (PMP) that forms quickly after mating begins and an anterior MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 62 publications
4
63
0
Order By: Relevance
“…The sperm‐transport hypothesis has received considerable support. When male anopheline mosquitoes were prevented from forming a plug through RNA interference, their sperm failed to reach the female's sperm storage organ and therefore did not fertilize any eggs (Rogers et al, ); a similar effect was observed in Drosophila (Avila et al, ). The sperm of male rats surgically prevented from forming a copulatory plug or who formed incomplete plugs generally failed to migrate past the vagina (Blandau, ,; Matthews and Adler, ; Toner et al, ; Cukierski et al, ; Carballada and Esponda, ).…”
Section: What Do Copulatory Plugs Do?mentioning
confidence: 95%
“…The sperm‐transport hypothesis has received considerable support. When male anopheline mosquitoes were prevented from forming a plug through RNA interference, their sperm failed to reach the female's sperm storage organ and therefore did not fertilize any eggs (Rogers et al, ); a similar effect was observed in Drosophila (Avila et al, ). The sperm of male rats surgically prevented from forming a copulatory plug or who formed incomplete plugs generally failed to migrate past the vagina (Blandau, ,; Matthews and Adler, ; Toner et al, ; Cukierski et al, ; Carballada and Esponda, ).…”
Section: What Do Copulatory Plugs Do?mentioning
confidence: 95%
“…They demonstrated that the mating plug ensures successful sperm storage, and sperm storage was severely inhibited without the plug‐forming enzyme transglutaminase. Similarly, the seminal fluid protein PEBme is required for effective mating plug coagulation and sperm storage in D. melanogaster (Avila et al, ).…”
Section: Sperm Aggregation At the Spermathecal Vestibulementioning
confidence: 99%
“…3). Further, the number of sperm in the seminal receptacle at 35min when females received Acp36DE FL was similar to females who received endogenous Acp36DE at the same time point (Avila et al 2015b). Females mated to Acp36DE CP1 males stored the most sperm, although they did not contain significantly more sperm than those mated to Acp36DE FL males.…”
Section: Resultsmentioning
confidence: 62%
“…We focused on sperm accumulation into the seminal receptacle at 35min ASM. At this time, sperm are rapidly entering the seminal receptacle (Manier et al 2010) and defects in sperm storage there are readily detected (Avila et al 2015b). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation